Boosting Alfalfa (Medicago sativa L.) Production With Rhizobacteria From Various Plants in Saudi Arabia - Daur, Ihsanullah; Saad, Maged M.; Eida, Abdul Aziz; Ahmad, Shakeel; Shah, Zahid Hussain; Ihsan, Muhammad Z.; Muhammad, Yasir; Sohrab, Sayed S.; Hirt, Heribert (Frontiers in Microbiology, 2018)
This study focused on rhizobacteria with a holistic vision of promoting sustainable crop production in arid regions of Saudi Arabia. The study isolated 17 rhizobacteria from tightly root-adhering soil of various plants at Hada Al-sham in Saudi Arabia, then characterized for plant growth promoting (PGP) traits. All the 17 rhizobacterial isolates were confirmed as PGPR by classical biochemical tests. The strains were then identified using 16S rDNA gene sequence analyses. According to 16S rDNA sequencing, the strains were classified into three different genera: Bacillus, Acinetobacter, and Enterobacter. Subsequently, the strains were assessed for their ability to improve physiology, nutrient uptake, growth, and yield of alfalfa plants grown under desert agriculture conditions. The field trials were conducted in a randomized complete block design. Inoculation of alfalfa with any of these 17 strains improved relative water content; chlorophyll a; chlorophyll b; carotenoid contents; nitrogen (N), Phosphorus (P), and Potassium (K) contents; plant height; leaf-to-stem ratio; and fresh and dry yields. Acinetobacter pittii JD-14 (GenBank ID: KY941126) was most effective, as it was recorded with highest fresh and dry yields of alfalfa, 80.2 and 26.4 tons respectively compared to un-inoculated control where fresh and dry yields of alfalfa were recorded 56.7 and 19.7 tons respectively. Nevertheless, all strains enhanced crop traits when compared to controls. Overall, this study indicates that these desert PGPR strains could be used to develop an eco-friendly biofertilizer for alfalfa and probably for other crop plants to enhance sustainable production in arid regions. However, further studies will be needed to screen them for virulence factors before developing for commercial application.